PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN BELANJA MODAL TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) (Survei Pada Kabupaten/Kota di Sulawesi Tengah) - Yanto, Edi (Katalogis, 2018)
This study intends to determine the influence of local revenues (X1) and capital expenditures (X2) on Human Development Index (HDI) (Y). The main issue is to examine simultaneous and partial influence of local revenues and capital expenditures on human development index in districts/cities in Central Sulawesi. Instrument of study is the documentÂ APBD reports of Central Sulawesi in 2012-2015 by using ratio as the scale of measurement and percentage on human development index of Central Sulawesi in 2013-2016 with ratio as the scale of measurement. Populasi of study consists of 13 districts/cities in Central Sulawesi by taking a sample of 11 districts/cities based on certain criteria. The results indicate that local revenues and capital expenditures simultaneously have significant influence on HDI in district/cities in Central Sulawesi with significance level of 0,998229 or 99,8%. This figure is relevant with the result of probability value (F-statistics) of 0,000000 less than sig. Î± = 5% (< sig. Î± = 5%). Local revenues has partial and significant influence on HDI in districts/cities in Central Sulawesi with significant probability level (t-statistics) Log (local revenues) equals to 0,0000 that less than sig. Î± = 5% (0,0000<0,05) and can be interpreted with significant level of â‰¥ 95%. Capital expenditures has partial and non-significant influence on HDI in districts/cities in Central Sulawesi with significant probability level (t-statistics) Log (capital expenditures) equals to 0,1809 that is more than sig. Î± = 5% (0,1809 > 0,05) and can be interpreted with significant level of < 95%.